1982
DOI: 10.1007/bf00151617
|View full text |Cite
|
Sign up to set email alerts
|

Statistical properties of MHD fluctuations associated with high-speed streams from Helios-2 observations

Abstract: Eielios 2 magnetic data have been used to derive scveraa y a itivi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
110
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(124 citation statements)
references
References 19 publications
12
110
2
Order By: Relevance
“…In fact, we have the possibility to analyse high and low velocity periods that are well known in literature. In particular, the time intervals, referring to fast wind, correspond to the same stream which is observed after two solar rotations (Bavassano et al, 1982). Moreover, Bruno et al (1985), studying the same intervals, have shown that Alfvénicity rapidly evolves with heliocentric distances, being larger at 0.3 AU than at 1 AU.…”
Section: Waiting-time Dependence On Heliocentric Distancementioning
confidence: 54%
“…In fact, we have the possibility to analyse high and low velocity periods that are well known in literature. In particular, the time intervals, referring to fast wind, correspond to the same stream which is observed after two solar rotations (Bavassano et al, 1982). Moreover, Bruno et al (1985), studying the same intervals, have shown that Alfvénicity rapidly evolves with heliocentric distances, being larger at 0.3 AU than at 1 AU.…”
Section: Waiting-time Dependence On Heliocentric Distancementioning
confidence: 54%
“…The upper panel of Fig. 6 shows the histogram of magnetic field and σ 2 xyz the standard deviation of the magnetic field intensity and the trace of the variance matrix of the components, respectively (Bavassano et al, 1982a;Bruno and Bavassano, 1991). Both panels clearly indicate that the two regions characterized by σ C ∼1 and σ R ∼0 and σ C ∼0 and σ R ∼−1, respectively, show the lowest magnetic compressive level.…”
Section: Discussionmentioning
confidence: 95%
“…Anisotropy of MHD fluctuations in the solar wind, due to the background magnetic field transported away from the sun by the plasma flow [15,16], has been investigated through the minimum variance analysis [17]. This method gives informations about the energy distribution among the different components of magnetic fluctuations.…”
mentioning
confidence: 99%